Representation Of Plastic Waste Care On Ecoton Instagram - Subrata, Isa Darwisy; Febriana, Poppy (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Social media platforms like Instagram serve as spaces for users to share content, express their interests, and engage with others, with features such as posts and Instagram Stories facilitating diverse forms of communication. Specific Background: Ecological Observation and Wetland Conservation (ECOTON), a foundation focused on wetland conservation, particularly in managing the Brantas River, utilizes Instagram to promote environmental awareness, particularly concerning plastic waste. Knowledge Gap: While numerous studies examine the role of social media in environmental activism, there is limited research on how non-governmental organizations (NGOs) like ECOTON leverage Instagram to convey messages about plastic waste management. Aims: This research aims to describe and interpret the meanings embedded in ECOTON's Instagram posts, specifically analyzing the signs and symbols in their photos and videos using Charles Sanders Pierce’s semiotic theory. Results: The findings reveal that ECOTON effectively uses Instagram to raise awareness about plastic waste, presenting their messages comprehensively and resonating with the public through a strategic use of visual and symbolic representation. Novelty: This study contributes to the understanding of how environmental NGOs harness social media to frame ecological issues, emphasizing the role of visual semiotics in shaping public consciousness. Implications: The research underscores the potential of Instagram as a powerful tool for environmental advocacy, highlighting its capacity to influence public perception and encouraging further research into social media strategies for ecological movements. Highlights: ECOTON effectively uses Instagram to raise public awareness about plastic waste. Semiotic analysis reveals deeper meanings in visual and symbolic content. Instagram is a powerful tool for environmental advocacy and shaping public perception. Keywords: Instagram, ECOTON, Plastic Waste, Semiotics, Environmental Awareness